2021
DOI: 10.3390/ijerph182111651
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of the PILCAST Questionnaire: Understanding Parents’ Intentions to Let Their Child Cycle or Walk to School

Abstract: Children generally do not meet the recommendation of 60 min of daily physical activity (PA); therefore, active school transportation (AST) is an opportunity to increase PA. To promote AST, the involvement of parents seems essential. Using the theory of planned behavior (TPB), the aim was to develop and validate the PILCAST questionnaire to understand parents’ intentions to let their child cycle or walk to school. Cross-sectional sampling was performed, where 1024 responses were collected from parents. Confirma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…In previous studies, the involvement of the end-users (children and their parents) throughout the whole process has been a cornerstone (Rutberg and Lindqvist, 2018a;Savolainen et al, 2020) in addition to the use of gamification and games (Kostenius et al, 2018;Laine et al, 2022;Oyelere et al, 2022). As previously stated, the role of parents as "gate-keepers" and the need to address parental concerns have been described in previous research and also in several of our intervention studies (Forsberg et al, 2020(Forsberg et al, , 2021Rutberg and Lindqvist, 2018). One intervention part attempting to address parents' perception of risk, has been information during parental meeting regarding the positive outcomes of AST and concerns about its perceived risks .…”
Section: Introductionsupporting
confidence: 57%
“…In previous studies, the involvement of the end-users (children and their parents) throughout the whole process has been a cornerstone (Rutberg and Lindqvist, 2018a;Savolainen et al, 2020) in addition to the use of gamification and games (Kostenius et al, 2018;Laine et al, 2022;Oyelere et al, 2022). As previously stated, the role of parents as "gate-keepers" and the need to address parental concerns have been described in previous research and also in several of our intervention studies (Forsberg et al, 2020(Forsberg et al, , 2021Rutberg and Lindqvist, 2018). One intervention part attempting to address parents' perception of risk, has been information during parental meeting regarding the positive outcomes of AST and concerns about its perceived risks .…”
Section: Introductionsupporting
confidence: 57%
“…Parents’ perceived confidence in their child’s AST positively related to their child´s AST in most studies, while a few reported no relationship (Table 7 ). Among the studies reporting a positive relation, Forsberg et al [ 29 ] reported that when PBC was divided into impeding and facilitating factors, only the latter was important for parents. Sims and Bopp [ 100 ] further reported that parents’ PBC was positively related to AST but found no relationship between parents’ self-efficacy and AST.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies reported a positive relationship between a parent’s attitude and their child’s use of AST, while a few found no relationship (Table 7 and 8 ). Among the studies reporting a positive relation, Forsberg et al [ 29 ] concluded that positive attitudes were an important factor for parents’ intention to let their children cycle to school, but not regarding parents’ intention to let their children walk to school. Also, Corral-Abos [ 18 ] only found a positive relationship between children’s AST and mother’s attitudes, but not fathers’.…”
Section: Resultsmentioning
confidence: 99%
“…The validity and reliability of 11 constructs and 93 items are demonstrated through the use of an active school transport (AST) questionnaire to measure parental intentions in a developing country. The role of parents as representatives of children's decision-makers in choosing transportation to school is significant [75]; therefore, the validity and reliability of the instrument scale to understand parents' intentions to allow their children to cycle or walk to school are crucial, particularly in the context of developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire was constructed to test the TPB constructs (i.e., attitude, subject norm, description norm, perceived behavioral control, and intention) based on the methods of [73] and prior research on AST in children [23,38,41,74,75]. Attitude is measured by nine items (i.e., "If my child cycles/walks to school regularly, my child's independence will grow well").…”
Section: Theory Of Planned Behavior Subscalementioning
confidence: 99%